Use of azoximer bromide for treatment of children's inflammatory infections of respiratory system: a meta-analysis of controlled clinical studies - A. V. Karaulov; A. V. Gorelov (Журнал инфектологии, 2019)
Objective. The aim of this meta-analysis is to summarize clinical efficacy of azoximer bromide for treatment of inflammatory respiratory infections in children and adolescents based on data from controlled clinical trials.Materials and. methods. In total 5 clinical studies with data from 542 patients aged. 3—18 years were selected, where effectiveness of therapy with addition of azoximer bromide to combination, therapy was compared, to standard, symptomatic treatment.Results. The results of the meta-analysis demonstrate that the addition of azoximer bromide from the first day to respiratory infections treatment in patients aged. 3-18 years helps to reduce temperature normalization, time [mean difference -1,92 day in favour of treatment with investigational drug (95% confidence interval 1,65; 1,15) according to the random effects model or -1,4 days (95% confidence interval 3,16; 0,67) according to fixed effects model]. Moreover azoximer bromide use in inflammatory respiratory infections treatment reduces the duration of fever and intoxication symptoms by 1,4 days in comparison with the control group (95% confidence interval 1,65; 1,15), headache by 0,53 days (95% confidence interval -0,91; -0,15), muscle and. joint pain by 1,59 days (95% confidence interval -2,1854; -1,0028) and catarrhal symptoms by 1,23 days (95% confidence interval 1,32; 1,14).Conclusion. Addition of azoximer bromide as nosotropic therapeutic agent to combination, therapy of respiratory diseases make possible to control intoxication, symptoms in a better way, reduces the morbidity of infectious and inflammatory process, has positive effect on immune mechanisms and causes almost no side effects.